Short version of the Zimbardo Time Perspective Inventory (ZTPI-25): Brazilian validation (Research, Society and Development, 2021)
Objective: to investigate the evidence of validity (of construct, structural and convergent) of a short version of the Zimbardo Temporary Perspective Inventory for the Brazilian population. Method: data were collected from 281 people living with HIV, seen at public health services. Exploratory factor analysis, confirmatory factor analysis and correlations were performed, resulting in the proposition of a short version containing 25 items. Results: ZTPI-25 was identified as the best option for the Brazilian population, with satisfactory adjustment, preservation of psychometric properties and theoretical premises of the original instrument. The structural validity was conferred by the homogeneity between the factors and the convergent validity was admitted by the correlations between the constructs, which presented significant. Conclusion: The ZTPI-25 preserves the psychometric properties of the original version, and as having the advantages of shorter application times, lower rejection rates and reduced unanswered questions when compared to other scales validated in Brazil.